231k views
14 votes
THanks again for the response.​

THanks again for the response.​-example-1

2 Answers

2 votes

Answer:

(-3, -2)

Explanation:

When the two lines intersect, f(x) = h(x)

2x + 4 = -1x - 5

Rearranging like terms together

3x = -9

x = -3

Substituting back into h(x) for x = -3

y = h(3) = 2(-3) + 4 = -2

So the point is (-3, -2)

User Taylor Austin
by
4.6k points
9 votes

Answer:

(-3,-2)

Explanation:

Equations are

  • y=2x+4
  • y=-x-5

Solve both

  • 2x+4=-x-5
  • 3x=-9
  • x=-3

On solving

  • y=3-5=-2

Graph is also attached if you need another way

THanks again for the response.​-example-1
User Belinda
by
5.0k points